An optimized nucleic acid isolation protocol for virus diagnostics in cassava (Manihot esculenta Crantz.) - Jiménez Polo, Jenyfer; Leiva Sandoval, Ana Maria; Olaya, Cristian A.; Acosta-Trujillo, Daniela; Cuéllar, Wilmer Jose (Elsevier, 2021)
Our group works on the detection and characterization of cassava viruses, supporting projects that involve large scale pathogen surveillance activities and resistance screening assays in multiple and remote locations. In order to comply with these applications, nucleic acid isolation protocols need to be cost effective, adjusted for samples that will stand long distance transport and harsh storage conditions, while maximizing the yield and quality of the nucleic acid extracts obtained. The method we describe here has been widely used and validated using different downstream tests (including, but not limited to, Rolling Circle Amplification and Illumina and Nanopore sequencing), but is currently unpublished. The protocol begins with milligram amounts of dry leaf samples stored in silica gel, does not require liquid Nitrogen nor phenol extraction and produces an average of 2.11 µg of nucleic acids per mg of dry tissue.